Case study and application of pre-computation technique for hashing cores aiming at high-throughput implementations - Michail, Harris; Kakarountas, Athanasios P.; Goutis, Costas E. (My University, 2005)
Hash functions are forming a special family of cryptographic algorithms, which are applied wherever message integrity and authentication issues are critical. Implementations of these functions are cryptographic primitives to the most widely used cryptographic schemes and security protocols such as SET, PKI, IPSec and VPN's. As time passes it seems that all these applications call for higher throughput due to their rapid acceptance by the market. In this work a new technique is presented for increasing frequency and throughput of all widely used hash functions - and those that will be used in the future- hash functions such as MD-5, SHA-1, RIPEMD (all versions), SHA-256, SHA-384, and SHA-512 etc. Comparing to conventional pipelined implementations of hash functions the proposed pre-computation technique leads to a 40%-25% higher throughput.
Keywords: Hardware; Cryptography; Extranets (Computer networks)